2018
DOI: 10.15517/rbt.v66i2.33421
|View full text |Cite
|
Sign up to set email alerts
|

Degradación de hojarasca y aporte de nutrientes del manglar en la Laguna Mecoacán, Golfo de México

Abstract: Leaf litter degradation and nutrient supply in the mangroves of Mecoacán Lagoon, Gulf of Mexico. Mangroves are ecosystems with a high primary productivity that is mainly driven mainly by degradation processes. Energy (nutrients) flows from mangroves toward adjacent zones and the surrounding aquatic environment. The objective of the present study was to estimate the daily degradation coefficient (k) of mangrove leaves in relation to physical-chemical soil factors and in situ nutrient supply (phosphorus and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
4
6
0
Order By: Relevance
“…The higher density of L. racemosa coincides with that found in basin mangroves where, with greater distance inland, the tidal influence decreases, and the density of R. mangle diminishes, while that of L. racemosa and A. germinans increases [32]. The mangrove species were consistent with those recorded in Tabasco by Torres et al [52] and Torres et al [53] and in Veracruz by Carmona-Díaz et al [54] and Moreno-Casasola et al [55], comprising three of the six mangrove species recorded in Mexico. The density of mangroves is a function of growth and developmental stage due to competition for crown space [52].…”
Section: Tree Densitysupporting
confidence: 89%
See 1 more Smart Citation
“…The higher density of L. racemosa coincides with that found in basin mangroves where, with greater distance inland, the tidal influence decreases, and the density of R. mangle diminishes, while that of L. racemosa and A. germinans increases [32]. The mangrove species were consistent with those recorded in Tabasco by Torres et al [52] and Torres et al [53] and in Veracruz by Carmona-Díaz et al [54] and Moreno-Casasola et al [55], comprising three of the six mangrove species recorded in Mexico. The density of mangroves is a function of growth and developmental stage due to competition for crown space [52].…”
Section: Tree Densitysupporting
confidence: 89%
“…The mangrove species were consistent with those recorded in Tabasco by Torres et al [52] and Torres et al [53] and in Veracruz by Carmona-Díaz et al [54] and Moreno-Casasola et al [55], comprising three of the six mangrove species recorded in Mexico. The density of mangroves is a function of growth and developmental stage due to competition for crown space [52]. The highest density associated with L. racemosa is consistent with that reported in Colima, Mexico, by Téllez-García et al [56] and by Torres-Fernández et al [54], who reported it as the species with the highest density.…”
Section: Tree Densitysupporting
confidence: 88%
“…If the current deforestation rate does not change, all mangroves could be gone by next century [21]. The high primary production in mangroves is generally attributed to leaf degradation processes [22], which recycle nutrients within the ecosystem [23]. Mangroves play a significant role in N dynamics, which indicates that anthropogenic nutrient enrichment may cause extensive impact in the N cycling [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, comparisons of decay rates between wet and dry seasons may provide some insights. Several researchers have found that mangrove leaves decayed faster in the wet season than in the dry season (Aké‐Castillo et al, 2006; Chanda et al, 2016; Torres et al, 2018; Twilley et al, 1997; Van Vinh et al, 2020), whereas Kamal et al (2020) found that litter exhibited higher decay rates in the dry season. When leaves are wetted, there is an initial rapid leaching stage of the most labile OM and water‐soluble compounds (Mfilinge et al, 2002) are broken down due to fungal and bacterial action.…”
Section: Discussionmentioning
confidence: 99%